2010
DOI: 10.1097/tp.0b013e3181e98d51
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Function After Genetically Engineered Pig Liver Transplantation in Baboons

Abstract: Background If ‘bridging’ to allotransplantation is to be achieved by a pig liver xenograft, adequate hepatic function needs to be assured. Methods We have studied hepatic function in baboons after transplantation of livers from α1,3-galactosyltransferase gene-knockout (GTKO,n=1) or GTKO pigs transgenic for CD46 (GTKO/CD46,n=5). Monitoring was by liver function tests and coagulation parameters. Pig-specific proteins in the baboon serum/plasma were identified by Western blot. In 4 baboons, coagulation factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 31 publications
3
66
0
Order By: Relevance
“…Early work demonstrated reasonable xenogeneic production of essential proteins, but with survival limited to a week or less due to profound thrombocytopenia, bleeding, and notable cholestasis, thought to be due to interspecies incompatibilities. 1 Although previous work in our laboratory did extend survival up to 9 days after liver xenotransplantation (LXT), recipient baboons required intensive platelet transfusions, antifibrinolytic agents, and on average 70 to 80 mLs of packed red blood cell (PRBC) transfusions daily. 2 Based upon our observation of marginal coagulation factor production in baboon recipients of porcine livers, we recently developed a novel approach utilizing the continuous administration of exogenous human coagulation factors after LXT.…”
mentioning
confidence: 99%
“…Early work demonstrated reasonable xenogeneic production of essential proteins, but with survival limited to a week or less due to profound thrombocytopenia, bleeding, and notable cholestasis, thought to be due to interspecies incompatibilities. 1 Although previous work in our laboratory did extend survival up to 9 days after liver xenotransplantation (LXT), recipient baboons required intensive platelet transfusions, antifibrinolytic agents, and on average 70 to 80 mLs of packed red blood cell (PRBC) transfusions daily. 2 Based upon our observation of marginal coagulation factor production in baboon recipients of porcine livers, we recently developed a novel approach utilizing the continuous administration of exogenous human coagulation factors after LXT.…”
mentioning
confidence: 99%
“…(19, 20) Ekser et al reported the first results of LXT with GTKO pigs as well as those polytransgenic for GTKO and CD46. (15, 21) Clinically, this study suggested that survival from 4–7 days could be achieved and during this time, the liver xenograft was capable of adequate protein synthesis (including albumin, fibrinogen, haptoglobin, plasminogen, and coagulation factors). (15, 21) Unfortunately, however, recipients developed profound thrombocytopenia which began to develop within an hour after reperfusion and eventually resulted in spontaneous hemorrhage which did not allow for survival beyond one week.…”
Section: Laboratory Experience With Liver Xenotransplantationmentioning
confidence: 88%
“…(15, 21) Clinically, this study suggested that survival from 4–7 days could be achieved and during this time, the liver xenograft was capable of adequate protein synthesis (including albumin, fibrinogen, haptoglobin, plasminogen, and coagulation factors). (15, 21) Unfortunately, however, recipients developed profound thrombocytopenia which began to develop within an hour after reperfusion and eventually resulted in spontaneous hemorrhage which did not allow for survival beyond one week. (21) In a subsequent study of GTKO liver xenografts preformed by Kim et al, utilizing a different immunosuppression regimen (FIGURE 1), survival of 6, 8, and 9 days was accomplished.…”
Section: Laboratory Experience With Liver Xenotransplantationmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, even though some of the products of the pig liver seem to function adequately in NHPs [96], it is unlikely that the multiple products of the pig liver will fulfill all of the metabolic needs of the human recipient. Here again, in selected instances where it is essential to correct a deficiency, genetic manipulation of the source-pig may enable any discrepancies to be overcome.…”
Section: Expert Commentarymentioning
confidence: 99%